Theranostic Value of Multimers: Lessons Learned from Trimerization of Neurotensin Receptor Ligands and Other Targeting Vectors - Simone Maschauer; Jürgen Einsiedel; Dominik Reich; Harald Hübner; Peter Gmeiner; Hans-Jürgen Wester; Olaf Prante; Johannes Notni (MDPI AG, 2017)
Neurotensin receptor 1 (NTS1) is overexpressed on a variety of cancer entities; for example, prostate cancer, ductal pancreatic adenocarcinoma, and breast cancer. Therefore, it represents an interesting target for the diagnosis of these cancers types by positron emission tomography (PET) [...]